A Present and a Non-Present Body—Experiencing the Body by Female Sex Workers in Commercial Sexual Relations - Ślęzak, Izabela (Qualitative Sociology Review, 2018)
Making women’s bodies accessible to men in the commercial context is related to specific ways of experiencing it. The purpose of the article is to discuss the category of a non-present, selectively present, and present body, which refers to ways in which female sex workers experience their bodies during commercial sex acts. There will also be conditions listed that correspond to the occurrence of each of these categories. The article is based on qualitative data (mainly unstructured interviews), which were analyzed in accordance with the procedures of grounded theory methodology.